Public Investment, Public Finance, and Growth : The Impact of Distortionary Taxation, Recurrent Costs, and Incomplete Appropriability - Adam, Christopher (IMF Working Papers; Working Paper ;, 2014)
Effective public investment requires governments to address the "recurrent cost problem" to ensure operations and maintenance (O and M) expenditures are sufficient to sustain the flow of productive public capital services to private factors of production. Building on the model of Buffie et al (2012), this paper explores the macroeconomic implications of this recurrent cost problem and its resolution in a context that recognizes that taxation is distortionary. The model is also used to examine stylized fiscal reforms including the replacement of a distortionary output tax with a uniform consumption tax and budgetary reforms that restore O and M expenditures to their efficient levels. These experiments are stylized but clearly demonstrate the material consequences of the tax and public expenditure structures for growth and debt sustainability in low-income countries.